2020
DOI: 10.1108/prr-09-2020-0028
|View full text |Cite
|
Sign up to set email alerts
|

Does Sukuk financing boost economic growth? Empirical evidence from Southeast Asia

Abstract: Purpose This paper aims to investigate empirically whether Sukuk financing is boosting the economic growth in Southeast Asia within the framework of the endogenous growth model. Design/methodology/approach This paper applied dynamic panel one-step system generalized method of moments as an optimal estimation approach to investigate the impact of Sukuk financing on economic growth in Southeast Asia spanning from 2013Q4–2019Q3. Sukuk financing was proxied by the total issued Sukuk holdings, while economic grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 49 publications
3
27
0
1
Order By: Relevance
“…As well, Tabash and Anagreh (2017) stated that Islamic finance has enhanced investment and economic growth. Besides, Kassim (2016), Boukhatem and Moussa (2018), Ledhem (2020), Ledhem and Mekidiche (2020) and Ledhem and Moussaoui (2021) confirmed that economic growth is endorsed by the factor of Islamic finance, which has been used as an exogenous factor within the endogenous growth model.…”
Section: Islamic Finance In Turkeymentioning
confidence: 74%
“…As well, Tabash and Anagreh (2017) stated that Islamic finance has enhanced investment and economic growth. Besides, Kassim (2016), Boukhatem and Moussa (2018), Ledhem (2020), Ledhem and Mekidiche (2020) and Ledhem and Moussaoui (2021) confirmed that economic growth is endorsed by the factor of Islamic finance, which has been used as an exogenous factor within the endogenous growth model.…”
Section: Islamic Finance In Turkeymentioning
confidence: 74%
“…Furthermore, as reported by Azmat et al (2021), Islamic securities can depend on customers' emphasis on religiosity; this makes Islamic securities as attractive instruments for investors as other conventional assets which indicates that Islamic securities can replace conventional assets in the capital markets from this side also. Consequently, although Islamic capital markets are still small compared to the conventional capital markets (IIFM Sukuk Report, 2019, this paper indicates that Islamic capital markets are expected to be prosperous in the future as an alternative financial system that enriches economic growth through increasing the capital stock and investments, consistently with the expectations of Cevik and Bugan (2018), Ledhem (2020) and Yıldırım et al (2020).…”
Section: Discussionmentioning
confidence: 90%
“…In a recent study, Ledhem (2020) investigated the link between the financing of Islamic securities (Sukuk) and economic growth in all of Indonesia, Brunei Darussalam and Malaysia based on a quarterly sample from 2013Q4 till 2019Q3. Using panel system GMM, Ledhem (2020) examined the effect of Islamic securities on the gross domestic product (GDP) as the IES factor of economic growth. The findings indicated that Islamic securities had a positive impact on economic growth.…”
Section: Earlier Empirical Studiesmentioning
confidence: 99%
“…This relationship between Islamic finance and economic growth is an extension of the "supply-leading hypothesis" of Schumpeter identifications (Schumpeter and Redvers, 1934) and compatible with the "financial repression theory" of McKinnon (1973) and Shaw (1973), in which the financial development leads to economic growth. As well, Ledhem (2020) demonstrated that Islamic finance is promoting economic growth through Sukuk (Islamic bonds) markets in Southeast Asia as an exogenous factor within the model of endogenous growth. Besides, based on the study of Ledhem and Mekidiche (2020), Islamic finance is improving economic growth internationally as an exogenous factor in the model of endogenous growth.…”
Section: Prrmentioning
confidence: 99%